A review of ketamine’s role in ECT and non-ECT settings - Jankauskas V (Dove Medical Press, 2018)
Vytautas Jankauskas,1 Candace Necyk,2 James Chue,3 Pierre Chue4 1Department of Pharmacy, Grey Nuns Community Hospital, Edmonton, Alberta, Canada; 2Faculty of Pharmacy and Pharmaceutical Sciences, University of Alberta, Edmonton, Alberta, Canada; 3Department of Anesthesiology, State University of New York at Buffalo, Buffalo, NY, USA; 4Clinical Trials and Research Program, University of Alberta, Edmonton, Alberta, Canada Abstract: Up to 20% of depressed patients demonstrate treatment resistance to one or more adequate antidepressant trials, resulting in a disproportionately high burden of illness. Ketamine is a non-barbiturate, rapid-acting general anesthetic that has been increasingly studied in treatment resistant depression (TRD), typically at sub-anesthetic doses (0.5 mg/kg over 40 min by intravenous infusion). More recent data suggest that ketamine may improve response rates to electroconvulsive therapy (ECT) when used as an adjunct, but also as a sole agent. In the ECT setting, a dose of 0.8 mg/kg or greater of ketamine demonstrates improved reduction in depressive symptoms than lower doses; however, inconsistency and significant heterogeneity among studies exists. Clinical predictors of responses to ketamine have been suggested in terms of non-ECT settings. Ketamine does increase seizure duration in ECT, which is attenuated when concomitant barbiturate anesthetics are used. However, most studies are small, with considerable heterogeneity of the sample population and variance in dosing strategies of ketamine, ECT, and concomitant medications, and lack a placebo control, which limits interpretation. Psychotomimetic and cardiovascular adverse effects are reported with ketamine. Cardiovascular adverse effects are particularly relevant when ketamine is used in an ECT setting. Adverse effects may be mitigated with concurrent propofol; however, this adds complexity and cost compared to standard anesthesia. Long-term adverse effects are still unknown, but relevant, given recent class concerns for anesthetic and sedative agents. Keywords: ketamine, ECT, anesthesia, major depressive disorder